2013
DOI: 10.1063/1.4828820
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Si doping and stacking fault related luminescence in homoepitaxial m-plane GaN

Abstract: Si-doped GaN layers grown by metal organic vapor phase epitaxy on m-plane GaN substrates were investigated by low-temperature cathodoluminescence (CL). We have observed stacking fault (SF) related emission in the range of 3.29–3.42 eV for samples with moderate doping, while for the layers with high concentration of dopants, no CL lines related to SFs have been noted. Perturbation of the SF potential profile by neighboring impurity atoms can explain localization of excitons at SFs, while this effect would vanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…According to literature the emission at 360.6 nm (3.438 eV) is attributed to the recombination of excitons bound to basal plane stacking faults of type I 1 . , Similar has been found for a -plane and m -plane GaN. , …”
supporting
confidence: 72%
See 1 more Smart Citation
“…According to literature the emission at 360.6 nm (3.438 eV) is attributed to the recombination of excitons bound to basal plane stacking faults of type I 1 . , Similar has been found for a -plane and m -plane GaN. , …”
supporting
confidence: 72%
“…8,32 Similar has been found for aplane and m-plane GaN. 10,33 Basal plane stacking faults lead to cubic insertions in wurzite GaN. For this type of basal plane stacking, the formation of a thin quantum well with type-II band alignment has been predicted by Stampfl et al 28 While exciting hexagonal material several ten nanometers below the quantum well-like heterostructure, the diffusion of the generated carriers leads to an onset of the BSF luminenscence.…”
Section: Nano Lettersmentioning
confidence: 58%
“…The donor–acceptor pair emission (DAP) at ≈3.28 eV with two LO‐phonon replicas is seen only in the reference spectrum for the GaN epilayer and is not presented in the CL spectra of the GaN NWs; however, the YL band centered at ≈2.2 eV is much stronger in the case when the CL measurements were taken at the NWs facets. An additional peak at ≈3.31 eV can be seen for the CL spectra taken at points 1 and 2 for the NW oriented along the true[11true2¯0true] direction and is associated with basal plane stacking faults (SF) and previously observed in non‐polar GaN, Mg‐doped GaN, and vertically grown GaN nanorods . The SF‐related luminescence has not been observed in each point of the planar NWs; however, we conclude that the presence of the emission lines due to SF is more typical for the NWs oriented in the true[11true2¯0true] direction, thus, once again confirming that the structural quality is better for the NWs manufactured along the true[10true1¯0true] axis.…”
Section: Resultssupporting
confidence: 83%
“…Mei et al [7] confirmed this observation in CL/TEM experiments at the same specimen position. Several groups also observed this luminescence peak in SF-containing samples [13][14][15][16][17][18][19]. Proposed by Albrecht et al [12], a quantum well like potential is assumed for the origin of the BSF I 1 emission.…”
mentioning
confidence: 96%